Modelling and Measuring Structural Complexity of Prolog Program Based on Rule-Dependency - Alizam, Jonie (2005)
This thesis describes modelling and measuring structural complexity mesure of Prolog program based on rule-dependency. Rule-dependency can be defined as relationships or interaction between rules. Usually, Prolog program is constructed by rules. These rules are Horn clause subset of the clausal form of first-order predicate logic. It is believed that rule-dependency is significant element of complexity and this research investigates to corroborate the claim especially on how rule dependency can be used to model and model and measure Prolog's structural complexity. This research is motivated by the lack of measures developed for Prolog due to the implicit control flow and construct. This lack of explicit control flow and constructs precludes in adapting conventional measures to Prolog program. This thesis shall present models that can be used to partially solve this problem that can enable direct application of existing measures tp Prolog program. To do measurement four criteria are explicitly defined: (1) attribute of entity, (2) abstraction or model, (3) ordering relationships, and (4) order-preserving mapping. These criteria are based on representational approach of measurement theory. The model Prolog's control flow and construct are modelled in the second criteria, while the measure is achieved by completing the process from identification of entity and attribute into numbers.